The impact of the Poland foreign trade on its real CO2 emissions - Bartosz Fortuński (Economic and Environmental Studies (E&ES), 2017)
CO2 emissions are a global problem. This means that nothing or very little will change if only particular countries are involved. The purpose of this paper is the attempt to show the real CO2 emissions of the Poland as well as the impact of its trade on CO2 emissions in other countries in the world and in the EU in 2015. This study was conducted on the group of countries that are the major emitters of CO2 in the world including most of the EU members. Actual CO2 emissions were achieved by applying the actual emission factor. This takes into account the transfer of CO2 in export products and services as well as those imported by particular countries. It has turned out that the real CO2 emissions in the Poland are significantly lower from the gross values which represent the CO2 emissions in the particular countries. It is also important to indicate that isolated actions of a single country within the European Union itself do not deliver the intended global and regional target - positive changes in CO2 emissions reduction. The approach
Keywords: Q37; Q40; Q53; Q56; 330; the EU energy policy; CO2 emissions; exports and imports of the Poland